As metas do projeto político-pedagógico e o rendimento escolar: um estudo comparativo - Almeida, Jefferson Serozini (2017)
This project was developed as practical work for the Master’s Program in Management and Educational Practices (PROGEPE), following the Research Line of Intervention of Methodologies of Learning and Teaching Practices (LIMAPE) of Nove de Julho University. The central theme is dedicated to the goals established in the Political-Pedagogical Project (PPP) of two learning institutions in the same region, serving the same public, but presenting diverging results in official and classification evaluations proposed by the state government. The focus of the study is to verify the application of the practices described as the PPP action plan goals among high school students during the school years of 2014 and 2015, investigating their influence in the performance of students in the analyzed school units. The methodology used was bibliographic research in secondary source for composition of the work’s theoretical structure, and the proposal of a case study to validate the diagnostic in the final analysis. In conclusion, the existence of two scenarios with distinct priorities is identified: One unit is focused and pressured to comply with indexes and surpass goals proposed by the government, and the other unit is willing to sacrifice these results to seek out teaching that is closer to the reality of its students.